Long-Range Energy Transfer between Dye-Loaded Nanoparticles Observation and Amplified Detection of Nucleic Acids - Biswas, Deep Sekhar (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.